A Baculovirus Expression Vector Derived Entirely from Non-Templated, Chemically Synthesized DNA Parts - Christopher Nguyen; Amanda Ibe-Enwo; Jeffrey Slack (Viruses, 2023)
Baculovirus expression system1s are a widely used tool in recombinant protein and biologics production. To enable the possibility of genome modifications unconstrained through low-throughput and bespoke classical genome manipulation techniques, we set out to construct a baculovirus vector (>130 kb dsDNA) built from modular, chemically synthesized DNA parts. We constructed a synthetic version of Autographa californica multiple nucleopolyhedrovirus (AcMNPV) through two steps of hierarchical Golden Gate assembly. Over 140 restriction endonuclease sites were removed to enable the discrimination of the synthetic genome from native baculovirus genomes. A head-to-head comparison of our modular, synthetic AcMNPV genome with native baculovirus vectors showed no significant difference in baculovirus growth kinetics or recombinant adeno-associated virus production—suggesting that neither baculovirus replication nor very-late gene expression were compromised by our design or assembly method. With unprecedented control over the AcMNPV genome at the single-nucleotide level, we hope to ambitiously explore novel AcMNPV vectors streamlined for biologics production and development.